Further investigation on solant–rectenna‐based flexible Hilbert‐shaped metamaterials. Issue 3 (30th June 2020) - Elwi, Taha A.; Abdulqader, Sarah G.
Abstract : This study discusses the design of a low‐profile metamaterial‐based antenna consisting of a 3 × 5 array of Hilbert shaped unit cells organised as a rectangular patch. The antenna is backed by with a partial ground plane loaded with square electromagnetic band gap defects for energy harvesting applications in the context of ultra‐wideband self‐powered wearable wireless devices. The antenna is mounted on a 28 × 32 mm FR4 substrate, with a thickness of 0.394 mm, a relative permittivity of 4.2 and a loss tangent of 0.02. The antenna is also printed on a flexible solar panel for self‐powered devices through solant–rectenna output terminals. The proposed solant–rectenna is found to cover the frequency range from 0.8 up to 10 GHz. The I – V characteristics of the solar panel are measured with and without the antenna structure to realize low shadowing effects. After that, the solant radiofrequency (RF) port is connected to a rectifier circuit to create a rectenna port that collects the RF energy and converts it to an output DC voltage at 0.915 GHz. It is found that the proposed rectenna provides an output DC voltage of 1.42 V with a conversion efficiency of 90%.